Evaluating herbicidal risks of the fungicide tebuconazole: differential sensitivity of dicot and monocot macrophytes in freshwater mesocosms - Silvia Mohr; Mishal Antony; Valeska Contardo-Jara; Ulrike Scholz; Stefan Bader; Christian Polleichtner; Gertie Arts (Environmental Sciences Europe)
Abstract Background The triazole fungicide tebuconazole (TBZ) has plant growth regulatory properties and is used as such in, e.g., oilseed rape crop production. To date, very little is known about the phytohormonal effects of TBZ on macrophytes. There are only data for the monocot macrophyte Lemna sp. available in the literature, which indicate a moderate risk for macrophytes. However, dicot macrophyte species are known to generally be more sensitive to growth regulating pesticides, due to the phytohormonal effects of these substances. Therefore, this study aimed to investigate if TBZ may impact monocot and dicot aquatic macrophytes differently and to quantify these effects. Two in situ experiments were conducted as part of a comprehensive study in freshwater mesocosms to evaluate direct and indirect effects of TBZ on five macrophyte species, particularly comparing the dicot species Myriophyllum spicatum with monocot duckweed species and the macrophyte standing stock of the mesocosms. For this, six naturally established freshwater mesocosms were dosed once with six different concentrations of TBZ (5–5000 μg/L), two served as controls. Results The dicot M. spicatum was the most sensitive species with the lowest EC50 (14 d) of 228 µg/L TBZ. In contrast, the monocot broad-leaved pondweed Potamogeton natans and two duckweed species reacted far less sensitive in this study with Spirodela polyrhiza being the most sensitive monocot species (EC50 (14 d): 1487 µg/L TBZ). Shoots of M. spicatum, which were grown directly as standing stock in the mesocosms, developed strong growth deformities in the form of shorter stems and condensed leaf whorls during the course of the study in the higher TBZ treatments. This effect can be linked to the anti-gibberellic mode of action of TBZ. Conclusion The results of this study highlight that short-term in situ experiments are a valuable tool that can efficiently be integrated into comprehensive mesocosm studies investigating aquatic communities, in order to gain reliable ECx data for several non-standard macrophyte species with different growth forms under near-natural conditions. The results of this research underscore that for regulatory risk assessment of fungicides with a phytohormonal mode of action, dicot aquatic macrophytes need to be included in the first tier of the risk assessment.